Upaya peningkatan pengetahuan kesehatan reproduksi remaja dan pencegahan anemia pada remaja putri - Niken Meilani; Nanik Setiyawati (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
Adolescents were vulnerable phase to reproductive health problems such as unintended pregnancy, unsafe abortion, sexually transmitted infections (STIs) including Human Immunodeficiency Virus (HIV), sexual abuse and rape and anaemia. Previous study of Niken Meilani and Nanik Setiyawati in 2019 showed that the level of adolescent reproductive health knowledge majority in the poor category and the proportion of anaemia was high. The results showed that the provision of Fe supplement tablets had an effect on increasing haemoglobin levels with p=0.020, reproductive health information also increase the level of knowledge of respondents p=0.000. This Community service for 7th grade female students at SMP Muhammadiyah Plus Gunungpring Muntilan as many as 70 students. The purpose of this community service was to increase knowledge through providing information through WhatsApp groups and Instagram and to increase haemoglobin levels by giving anaemia Fe tablets. Monitoring of activities is carried out two-way communication through WhatsApp groups involving school guidance and counsellor teachers. The evaluation of the activities was carried out by measuring the knowledge scores of the pre-test and post-test, and it was found that there was an increase in knowledge by using a pair t-test analysis with p = 0.000. Ten blood-added tablets are given for 10 weeks with the monitoring of the teachers. Community service activities by providing information through WhatsApp and Instagram statistically increase students' knowledge about adolescent reproductive health.